RETRACTED: The type of sensitization to allergens in allergic patients in Ankara, Turkey - Şahin, Caner; Özcan, Müge; İriz, Ayşe and Murat Özcan, Kürşat and Selçuk, Adın and Olcay, Işıl and Ünal, Adnan (ENT Updates, 2014)
Objective: To present our prick test results that would reflect allergens prevalent in the Central Anatolia. Methods: Prick tests of the 1618 patients diagnosed with allergic rhinitis, atopic dermatitis, allergic conjunctivitis between January 2003 and May 2005 were included in the study. In epidermal skin prick test, sensitization to 21 allergens including trees, grasses, weeds, fungus, epithelium-hair, house dust and mites, latex, and food were evaluated. Results: Positive prick test results were obtained in 565 (34.9%) of 1618 patient. Sensitivity to prick tests were as follows; 372 (66%) were positive for grass pollens, 242 (43%) were positive for house dust and mites, 265 (47%) were positive for tree pollens, 71 (12.6%) were positive for epithelium-hair allergens, 96 (17%) were positive for weed pollens, 37 (6.7%) were positive for foods, 24 (4.3%) were positive for fungus, 26 (4.7%) were positive for latex allergens. Conclusion: Our data indicates that the most common allergens in Ankara are grass pollens, tree pollens and house dust and mites.